2014
DOI: 10.1016/j.clinph.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor adaptation and locomotor adaptive learning in Parkinson’s disease and normal aging

Abstract: Objective Locomotor adaptation enables safe, efficient navigation among changing environments. We investigated how healthy young (HYA) and older (HOA) adults and persons with Parkinson’s disease (PD) adapt to walking on a split-belt treadmill, retain adapted gait parameters during re-adaptation, and store aftereffects to conventional treadmill walking. Methods Thirteen PD, fifteen HYA, and fifteen HOA walked on a split-belt treadmill for ten minutes with one leg twice as fast as the other. Participants later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
75
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 31 publications
9
75
4
1
Order By: Relevance
“…Thus, regardless of medication state, the participants adapted step length asymmetry from EARLY to LATE in similar fashion to previous studies of persons with PD on medication [8] and healthy young and older adults [13] (Figure 3). The order in which the sessions were performed appears to have little effect on any of the conditions, with perhaps the exception of EARLY (Figure 4; statistical analyses comparing the participants tested while ON meds first to those tested while OFF meds first were not performed due to sample size limitations of n=5 in each subgroup).…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…Thus, regardless of medication state, the participants adapted step length asymmetry from EARLY to LATE in similar fashion to previous studies of persons with PD on medication [8] and healthy young and older adults [13] (Figure 3). The order in which the sessions were performed appears to have little effect on any of the conditions, with perhaps the exception of EARLY (Figure 4; statistical analyses comparing the participants tested while ON meds first to those tested while OFF meds first were not performed due to sample size limitations of n=5 in each subgroup).…”
Section: Resultssupporting
confidence: 52%
“…We have previously shown that an acute bout of SBT walking can at least temporarily alter step length asymmetry in persons with PD [8]. While not all persons with PD exhibit significant gait asymmetry, those affected by asymmetric walking patterns may benefit from SBT training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By making possible monitoring of subjects in more natural environments wearable system may provide more comprehensive information on mechanisms of asymmetry or symmetry between right and brain functions. This information may improve performance in sport [14], adaptive behavioral decisions that are based on lateralized skills [2], as well as may help to improve effectiveness of some healthcare interventions [15].…”
mentioning
confidence: 99%